How does supervisors’ developmental feedback affect Chinese employees’ work role performance? The roles of thriving at work and trait mindfulness - Xiushen Hu; Yanbo Zhang; Mengqiu Xia (Humanities & Social Sciences Communications)
Abstract In a volatile, uncertain, complex, and ambiguous (VUCA) world, the question of how to effectively harness employee role behaviour, such as proficiency, adaptability, and proactivity, is inciting heated discussion among academic societies, and it is a vital practical issue to address. Employing self-determination theory, this study examines the mechanisms by which supervisors’ developmental feedback influences employees’ work role performance. The two-wave survey data from 497 respondents obtained via hierarchical regression analyses reveal that supervisors’ developmental feedback positively impacts employee work role performance, that thriving at work plays a mediating role in the relationship, and that this mediating relationship has conditional effects on the moderator variable of trait mindfulness. These findings could enrich the understanding of the effects of supervisors’ developmental feedback on employees’ work role performance and provide insight about how to facilitate this process.